High‐performance polymer‐stabilized blue‐phase LCD with low driving voltage. Issue 1 (25th March 2013) - Ishitani, Tetsuji; Niikura, Yasuhiro; Ikenaga, Makoto; Kobayashi, Manabu; Kato, Momoko; Oe, Yuko; Nakano, Masaru; Shishido, Hideaki; Hirakata, Yoshiharu; Yamazaki, Shunpei; Kurosaki, Daisuke
Abstract We have developed a polymer‐stabilized blue‐phase LCD in which the diffraction wavelength of blue‐phase liquid crystal is in the ultraviolet region and which is driven at a low voltage of V100 = 27 V. Prototypes of 3.4‐in polymer‐stabilized blue‐phase LCDs were made, which include a highly reliable crystalline oxide semiconductor. We succeeded in fabricating not a test cell but a display having a contrast ratio higher than 1000 : 1 for the first time in the world.